Four-dimensional connectivity modelling with application to Australia's north and northwest marine environments. (March 2015) - Kool, Johnathan T.; Nichol, Scott L.
Abstract: A fully four-dimensional (3D × time) object-oriented biophysical dispersal model was developed to simulate the movement of marine larvae over semi-continuous surfaces. The model is capable of handling massive numbers of simulated larvae, can accommodate diverse life history patterns and distributions of characteristics, and saves point-level information to a relational database management system. The model was used to study Australia's northwest marine region, with attention given to connectivity patterns among Australia's north-western Commonwealth Marine Reserves (CMRs). Animations of larval movement near the Gascoyne canyon CMR, dispersal surfaces over depth and time for CMRs and Key Ecological Features in the northwest, as well as matrices of connectivity values among CMRs are shown. The matrices are further analysed to identify the sensitivity and elasticity of their values. The results generated by this model can aid in designing and managing marine protected area networks that incorporate extensive and complex benthic terrain (including the identification of marine 'corridors'), and for developing targeted field sampling strategies. Highlights: We provide open-source software written in Java for performing individual-based marine dispersal simulations. The software is capable of handling volumetric releases over time with three-dimensional flow (3D space × time) and benthic collision detection. The software is scalable, and was used to simulate over a billion particle objects, which were saved to a database for subsequent analysis. A case study for Australia's north and northwest marine planning regions is presented, using dispersal characteristics of ophiuroids.